2016
DOI: 10.1111/cxo.12393
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between visual acuity and central retinal (macular) thickness after interventions for macular oedema in diabetics: a review

Abstract: Purpose:The aim was to compare efficacy of treatments for diabetic macular oedema (DMO) from changes in visual acuity (VA) and central macular thickness (CMT). Methods: Peer-reviewed articles from 2004 to 2014 reporting intravitreal injections of bevacizumab (IVB), ranibizumab (IVR) or triamcinolone acetonide (IVTA) or laser photocoagulation therapy (LPT) provided data on pre-treatment (baseline) and final outcome measures. Net changes and relative changes (percentage) were assessed by linear regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(170 reference statements)
1
4
0
Order By: Relevance
“…Ganglion cell damage results from traction to the ganglion cell due to a greater CMT. A decrease in CMT with a concomitant increase in visual acuity is warranted by pharmacological treatment [34,35]. The current study demonstrated a significant decrease in CMT with ranibizumab biosimilar treatment, indicating improved disease outcomes and reflecting the results from the original pooled analysis.…”
Section: Discussionsupporting
confidence: 69%
“…Ganglion cell damage results from traction to the ganglion cell due to a greater CMT. A decrease in CMT with a concomitant increase in visual acuity is warranted by pharmacological treatment [34,35]. The current study demonstrated a significant decrease in CMT with ranibizumab biosimilar treatment, indicating improved disease outcomes and reflecting the results from the original pooled analysis.…”
Section: Discussionsupporting
confidence: 69%
“…Finally, the decrease in vessel density in the macula could be a result of the combined effects of PRP and the use of anti-VEGF therapy. However, the number of anti-VEGF injections was not different between the 2 groups of patients with diabetes, and numerous studies have shown that intravitreal injections of anti-VEGF did not cause a decreased vessel density or FAZ enlargement . We believe there is a low likelihood that these limitations could have affected the meaning of the role of the vessel density decrease in the DCC and especially in the role DCP plays in loss of VA.…”
Section: Discussionmentioning
confidence: 75%
“…16,17 However, a reduction in retinal thickness is only modestly correlated with an improvement in VA, and it has been reported that there is a large variation in VA for any given retinal thickness. [16][17][18] Furthermore, gradual deterioration of VA in the absence of macular thickening can occur over time. 19 As demonstrated in refractory and regressed DME, mean OCT measured retinal thickness may not show a change over an extended period of follow-up; however, it may show significant variation from visit to visit.…”
Section: Introductionmentioning
confidence: 99%